Tensorial biomorphometrics Continuum, discrete and statistical aspects - Publico, Andre Supnet (Columbia University, 2000)
The study of the form and form changes of biological structures is essential to understanding their functions and their adaptation to changing conditions. In the past three decades, developments in geometric morphometrics and in image acquisition and geometrical information extraction technologies have made the investigations of forms in intra- and interpopulation settings increasingly practical. While there are morphometric methodologies for landmark data, outline data or interlandmark distances representation, there is no one method that completely models biological structures. The focus of this dissertation is the development of a methodology for handling, not only the aforementioned form representations, but also the more general cases of multiboundary structures. It consists of a general mean form algorithm and a multiboundary-based tensorial morphometric technique.